2018
DOI: 10.1159/000493834
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-203 Modulates Wound Healing and Scar Formation via Suppressing Hes1 Expression in Epidermal Stem Cells

Abstract: Background/Aims: Little is known how miR-203 is involved in epidermal stem cells (ESCs) differentiation and scar formation. Methods: We first used luciferase assay to determine the interaction of miR-203 with the 3’-UTR in regulation of Hes1 expression. We then used flow cytometry to analyze the effects of miR-203 expression on the differentiation of ESCs to MFB by determination of CK15 ratio and α-SMA. To confirm the results of flow cytometry analysis, we used Western blot to examine the expression of α-SMA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 51 publications
(65 reference statements)
1
33
0
Order By: Relevance
“…However, the low specific expression of Hes1 leads to a limited proliferation of skin EpiSCs, impeding the epithelialization process. Thus, skin barrier function damage and abnormal hair development occur [79,80]. One of the explanations is that the Notch signaling pathway can regulate stem cell adhesion; the latter affects the biological microenvironment ("niche") of stem cells.…”
Section: Regulation Of the Effect Of Notch Signaling Pathway On Thementioning
confidence: 99%
“…However, the low specific expression of Hes1 leads to a limited proliferation of skin EpiSCs, impeding the epithelialization process. Thus, skin barrier function damage and abnormal hair development occur [79,80]. One of the explanations is that the Notch signaling pathway can regulate stem cell adhesion; the latter affects the biological microenvironment ("niche") of stem cells.…”
Section: Regulation Of the Effect Of Notch Signaling Pathway On Thementioning
confidence: 99%
“…miR-203 shows the highest expression level in the skin, as compared with other organs, and plays an important role in skin-healing processes. 30 Our results therefore suggest that miR-203-3p might also be involved in these processes in IgAV. In addition, the altered expression of miR-203 found in psoriasis 31 and rheumatoid arthritis 32 suggests its involvement in immune-mediated diseases.…”
Section: Discussionmentioning
confidence: 56%
“…We noticed that mild granulocyte infiltration, without signs of fibrinoid necrosis, was mostly present in clinically older or healing skin lesions. miR‐203 shows the highest expression level in the skin, as compared with other organs, and plays an important role in skin‐healing processes . Our results therefore suggest that miR‐203‐3p might also be involved in these processes in IgAV.…”
Section: Discussionmentioning
confidence: 64%
“…A decrease in its expression at the level of transcriptome and proteome after TNF inhibitor therapy has been confirmed (Skarmoutsou et al, ). Zhou et al ()) describe the key role of the HES1 gene in promoting stem cell proliferation and inhibiting their differentiation, which is important when rebuilding the skin barrier, scarring after injury, and injury. In this study, an increase in HES1 expression can be observed, which indicates that proliferation processes are induced under the influence of adalimumab.…”
Section: Discussionmentioning
confidence: 99%